Organizational Climate and Turnover in the Health Sector.The Case of the Korle-Bu Teaching Hospital in Ghana. - Adjei-Appiah, Susana (University of Waterloo, 2008)
The study examined organizational climate and turnover in the health sector of Ghana with particular reference to a case study on the country’s premier teaching hospital formally called Korle-Bu Teaching Hospital. In the light of high uncertainty in retention of healthcare workers in Ghana, despite the several interventions of government in providing incentives and infrastructure, the issue of employee turnover has attracted academic interest among several researchers globally and locally. Most researches on turnover related issues in the healthcare sector of Ghana have focused on the influence of employees’ overall job satisfaction. However, none has been able to neither explain nor investigate the influence of potent psychological features of the workplace on turnover. This study undertook a comprehensive review of the current state of employees’ turnover intentions in relation to the organizational climate and other working conditions prevalent at the Korle-Bu Teaching Hospital. The study was guided by the hypothesis that climate factors will emerge as a significant predictor of employees’ turnover intentions. A sample size of 80 employees was used for the study. Correlation and multiple regression analysis were used to analyze data obtained with a Likert scale designed questionnaire. The results of the study indicate that stress and organizational pride are the most proximal factors to employees’ intentions to quit. Further analysis identified influences on stress and organizational pride and pointed to management priorities for reducing employee turnover.
Keywords: ORGANIZATIONAL CLIMATE; TURNOVER; HEALTH SECTOR; Psychology